READER RESPONSE ANALYSIS IN A LITTLE LIFE NOVEL BY HANYA YANAGIHARA - Desri Maria Sumbayak; Adinda Dwi Putri Sihite; Fikry Prastya Syahputra (Universitas Negeri Semarang, 2026)
This research aims to analyze readers’ reactions to the plot of the novel, sensitive topics in the novel, and the way the author evokes readers’ imagination. The opportunity to analyze the novel from the viewpoint of the readers is presented by the positives and drawbacks noted by readers on social media. Fish’s theory of reader-response analysis in an interpretive community is then applied in this research. The participants of this study were six readers that are actively joined a book discussion over social media. In conducting this study, qualitative research design with research instruments in the form of Google Form questionnaire were employed. The result of this study shows that, generally, the readers expect an emotional and sad story from the novel and their expectations of the plot is fulfilled by the author. These pros and con’s opinion from the readers also represent the novel’s discussion and reviews on social media. The result implies that the novel’s tragic and melodrama story is the appeal of the novel itself, as the plot invites the readers to create mixed reactions that influence the novel’s popularity on social media when they reviewed it.